A mitochondria-targeted nitric oxide donor triggered by superoxide radical to alleviate myocardial ischemia/reperfusion injury. Issue 9 (27th November 2018) - Hou, Jingli; He, Haiyan; Huang, Saipeng; Qian, Meng; Wang, Jie; Tan, Xiaoli; Han, Guifang; Song, Yuguang; Xu, Zhelong; Liu, Yangping
Abstract : We report a mitochondria-targeted and superoxide-responsive nitric oxide donor with good protection against ischemia/reperfusion injury in H9c2 cells and isolated rat hearts. Abstract : A novel mitochondria-targeted superoxide-responsive nitric oxide donor was developed by incorporation of diphenylphosphinyl and triphenylphosphonium groups into diazeniumdiolate, enabling remarkable protection against ischemia/reperfusion injury in H9c2 cells and isolated rat hearts.